Fibromyalgia Management with Homeopathy - Wandile, Pranali M. (Homœopathic Links, 2017)
Fibromyalgia is one of the most common genetically inherited chronic affective spectrum disorders (ASD). Other ASD disorders are psychiatric and medical conditions such as irritable bowel syndrome (IBS), migraine, cataplexy—attention-deficit/hyperactivity disorder, bulimia nervosa, dysthymic disorder, generalised anxiety disorder, major depressive disorder (MDD), obsessive-compulsive disorder, panic disorder, posttraumatic stress disorder, premenstrual dysphoric disorder, rheumatoid arthritis, and social phobia. Apart from genetic factors, neuroendocrine, autonomic nervous system abnormalities, psychosocial variables and environmental stressors contribute in the pathophysiology of fibromyalgia and other associated disorders. In this article, we reviewed etiology, pathophysiology, maintaining and triggering factors, and various treatment options for fibromyalgia. Apart from the pain management, this condition can be managed by ancillary method of treatment. However, due to the genetic cause of the disease, there is very little to offer for its complete cure. Homeopathic miasmatic treatment focuses on the genetic cause of the disease for its complete annihilation while also providing various acute remedies for the temporary pain management. We reviewed homeopathy treatment management and various remedies, which have much to offer for this chronic condition while considering its genetic, triggering and maintaining factors.
Keywords: Affective spectrum disorders; Fibromyalgia; Homeopathy